Development of Talk Button Media as an Audio Aid to Support Orientation and Mobility for Students with Visual and Intellectual Disabilities in Special Schools - Muhamad Aflaha Rijal; Pujaningsih Pujaningsih; Monika Nur Edlina; Resvi Fitri (FKIP - Universitas Riau, 2026)
Education for students with multiple disabilities with visual impairment (MDVI) requires accessible support to promote independence, particularly in orientation and mobility (O&M). In special schools, MDVI students often have difficulty recognizing rooms independently and rely heavily on verbal guidance from teachers. Although Braille-based signage is commonly used, it is not always effective because some MDVI students have limited Braille skills and working memory constraints. This study aimed to develop and examine the feasibility and initial usability of the Talk Button, an audio-based room marker designed to support O&M for MDVI students. The research employed a Design and Development Research (DDR) approach including needs analysis, product design, development, expert validation, and limited usability trials. Validation involved a material expert, a media expert, and a special education practitioner using a five-point Likert scale. The results showed that the Talk Button was considered feasible to very feasible. A limited trial with one MDVI student indicated that the student could operate the device and respond to the audio cues with minimal assistance. Overall, the Talk Button shows potential as an accessible room marker for MDVI students.